N.Y. Const. art. XL (April 20, 1777) - (:unkn) unknown (My University, 1777)
This convention therefore, in the name and by the authority of the good people of this State, doth ordain, determine and declare, that the militia of this State, at all times hereafter, as well in peace as in war, shall be armed and disciplined, and in readiness for service. That all such of the inhabitants of this State, being of the people called Quakers, as from scruples of conscience may be averse to the bearing of arms, be therefrom excused by the legislature; and do pay to the State such sums of money in lieu of their personal service, as the same may, in the judgment of the legislature, be worth: And that a proper magazine of warlike stores, proportionate to the number of inhabitants, be forever hereafter at the expense of this State, and by acts of the legislature, established, maintained, and continued in every county in this State.
Keywords: ARMED FORCES